Adults, computers and problem solving : what ́s the problem? - Organisation for Economic Co-operation and Development (OECD skills studies, ISSN 2307-8723, 2015)
Summary.
Keywords: oppiminen : arviointi : OECD-maat; osaaminen : arviointi : OECD-maat; aikuiskoulutus; tieto- ja viestintätekniikka